Collection of nanoparticles using novel filter process by edm - Irshad Ahamad, Khilji; Siti Nadiah, Mohd Saffe (2021)
Synthesis of nps used toxic chemical process. high time consuming. costly. skilled manpower required. still edm not used for nps generation